2010
DOI: 10.3844/crpsp.2010.75.81
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress and Family Difficulties of Working Women

Abstract: Problem statement: Work and family are the two most important aspects in women's lives. Balancing work and family roles has become a key personal and family issue for many societies. There are many facets in working mother's lives that subject to stresses. They deal with home and family issues as well as job stress on a daily basis. Imbalance between work and family life arises due to a number of factors. Various factors appear to strengthen the brunt of pressure on women. The question was raised whether there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…A similar was obtained by Almeida and Kessler [32], Tsaur and Tang [38], and Zarra-Nezhad, Moazami-Goodarzi, Hasannejad, and Roushani [39], who concluded that, despite the increasing career opportunities, women still face challenges at the workplace as well as want fundamental changes in their family adaptability and cohesion, WS and economic status. In a recent study, O'Neill and Davis [27] showed no significant difference based on gender, although this does not necessarily indicate the absence of such differences in the hotel industry in general.…”
Section: Test Of Hypothesessupporting
confidence: 72%
“…A similar was obtained by Almeida and Kessler [32], Tsaur and Tang [38], and Zarra-Nezhad, Moazami-Goodarzi, Hasannejad, and Roushani [39], who concluded that, despite the increasing career opportunities, women still face challenges at the workplace as well as want fundamental changes in their family adaptability and cohesion, WS and economic status. In a recent study, O'Neill and Davis [27] showed no significant difference based on gender, although this does not necessarily indicate the absence of such differences in the hotel industry in general.…”
Section: Test Of Hypothesessupporting
confidence: 72%
“…The stress experienced by women is higher as compared to men (Zappert and Weinstein, 1985; Miller and Green, 1985; Zarra-Nezhad et al , 2010). The stressors experienced by them are multiple roles, discrimination and stereotyping (Gyllensten and Palmer, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perhaps even when mothers do not work outside the home, they are confronted with high levels of stress ranging from carrying out household duties, motherhood and wifehood. As a result, job and family responsibilities become more complex, and the unshared work load by these mothers’ spouses frequently causes stress (Maryam et al, 2010). Now that many of them are in paid jobs, they have not abandoned their roles in their families (Kayode et al, 2012).…”
Section: Introductionmentioning
confidence: 99%